Semiconductor advanced packaging - Lau, John H. (Springer, 2021)
The book focuses on the design, materials, process, fabrication, and reliability of advanced semiconductor packaging components and systems. Both principles and engineering practice have been addressed, with more weight placed on engineering practice. This is achieved by providing in-depth study on a number of major topics such as system-in-package, fan-in wafer/panel-level chip-scale packages, fan-out wafer/panel-level packaging, 2D, 2.1D, 2.3D, 2.5D, and 3D IC integration, chiplets packaging, chip-to-wafer bonding, wafer-to-wafer bonding, hybrid bonding, and dielectric materials for high speed and frequency. The book can benefit researchers, engineers, and graduate students in fields of electrical engineering, mechanical engineering, materials sciences, and industry engineering, etc.